Architecture for performance - exploring the relationship between architecture, dance and the city - Manhiça, Luana (School of Architecture, Planning and Geomatics, 2023)
The focus of this investigation is the relationship between architecture and dance. The main concern is the challenge of translating dance to enhance architectural design, questioning how dance can inspire and unlock a potential in architecture through scale and movement of the body at various scales. Dance can be seen in two ways which relate and are parallels to architecture: for its interiority, the entertainment (escapist) value of dance which relates to architectural privacy; as well as for its exteriority, an activist (commentary) approach which relates to the public nature of architecture. The method I use to address this is a speculative design proposal of a dance school and theatre to test the ideas, which has Jazzart Dance Theatre as its imagined main stakeholder. The main topics are challenging the relationship between private and public space, architecture as performing art as well as an interest in accessibility (right to the city) through the movement of bodies from private entertainment into the public realm bringing connections. There is a tertiary interest in adaptive reuse which has the potential to create unique interiority and is sustainable. The key literature is ‘The Right to the city' by David Harvey, ‘The Production of Space' by Henri Lefebvre and ‘Architecture and disjunction' by Bernard Tschumi. The site where this design takes place in is the East City in Cape Town City Centre, at the corner of Harrington and Albertus Street. The site offers opportunities for claiming public space through activist performance in Harrington Square, which is re-imagined as public space; adding the nearby Fugard Theatre as an extension of the campus as well as a unique inner world with old and new buildings. The design provides escape whilst also creating a constant dialogue with the outside world.